Volumetric technique of a neutron probe calibration - Encarnação, Fernando; Carneiro, Clemente; Dall'Olio, Attílio; Vachaud, Georges (Pesquisa Agropecuaria Brasileira, 1991)
A new technique for neutron probe calibration was applied for three soils (Podzolic, Litolic and Alluvial). In the laboratory experiments, soil were stored in drums and packed under similar conditions. During the experiments, water was transferred to the drums from a Mariotte container that maintained a water table at 0.1 m from the bottom of the drum. The amounts of water transferred by capillarity were significantly correlated to the integrals of count ratio along the height of the drum. Under field conditions, the neutron probe calibration was obtained using a special arrangement hat prevented the lateral movement of water around the access tube of the neutron probe.
Keywords: water content; bulk density; stored water; capillarity